APPENDIX: 'THE TENN CIRCLES', 1569. (18th December 2015) - Unknown
Abstract : The Tenn Circles or Provinces of the Empire, and what Horsemen, and ffootemen[, ] everie one is bound to Contribute in all necessarie affayres for the State of the Empire, where is to be noted that the Protestantes in the same, doe double their Contribucion.